Correlation between weight-adjusted-waist index and hypertension in the US population: based on data from NHANES 2005–2018 - Huang, Anwu; Lin, Bin; Jia, Zhuyin; Ji, Xiaojun; Chen, Yalong (Frontiers in Cardiovascular Medicine, 2024)
ObjectivesThis study aimed to investigate the association between the weight-adjusted waist index (WWI) and the prevalence of hypertension in U.S. adults.MethodsData were sourced from the National Health and Nutrition Examination Survey (NHANES) spanning 2005–2018. In our cross-sectional study, we focused on the non-institutional U.S. population over the age of 18 from various communities in the United States. WWI is derived by dividing waist circumference by the square root of body weight. The definition of hypertension was based on self-reported history of hypertension, antihypertensive drug use, and blood pressure measurements. Participants without complete information on WWI and hypertension were excluded. The independent relationship and consistency between WWI and hypertension were assessed through weighted multivariate regression. The Pearson correlation test was used to detect the association between WWI and BMI. Subgroup analyses were used to verify the stability of the relationship between WWI and the prevalence of hypertension, and interaction tests were also conducted by gender, age, smoking, and triglycerides.ResultsAmong the 37,299 participants included, the hypertension prevalence was 33.9%. After adjusting for confounding variables, WWI demonstrated a significant association with hypertension. Individuals in the top quarter of WWI had a 2.27fold higher chance of hypertension prevalence compared with the bottom quarter (OR = 2.27, 95% CI 1.97–2.61; P < 0.0001). Subgroup analysis highlighted that this association was particularly pronounced in males aged ≤60 years.ConclusionThe findings underscore a robust correlation between elevated WWI and a heightened risk of hypertension, especially in males aged ≤60 years.